From digital voices to vaccine choices: increasing female vaccine acceptance in Sudan through social listening - Ahmed, Islam; Ali, Hiba; Ali, Sehrish; Van Woerden, Simon; Hanna-Amodio, Antonio; Chen, Katie; Onitolo, Elizabeth; Gillespie, Amaya (Frontiers in Global Women's Health, 2024)
The early COVID-19 vaccine rollout in Sudan experienced a gender disparity in vaccine uptake, with women accounting for less than 40% of vaccinations after four months of vaccine access. Initial analysis revealed that demand generation approaches were not sufficiently tailored to address the challenges and concerns of women. Using real-time social media monitoring, also known as social listening, to understand this inequity, we used an analytical tool called “Talkwalker” to track public sentiment and engagement regarding vaccination on social media platforms. The data captured subsequently informed a gender-responsive messaging campaign on social media that directly addressed specific concerns of Sudanese women. Within one week of the campaign's onset in September 2021, we observed a 144% increase in women's COVID-19 related social media engagement. Subsequent campaigns further enhanced women's engagement from 31% to between 35%–47%. Two subsequent campaigns in January and February/March 2022 were complemented with in-person activities, such as group meetings with community members and home visits by health promoters. Women's vaccination rates increased by 9% while the first two campaigns were live. System constraints hindered data linkages for the third campaign. These findings demonstrate the value of integrating real-time feedback with large-scale social media campaigns and the potential of linking online and offline strategies to further refine interventions, particularly in a conflict-prone and low-income country context. Our experience reinforces the notion that “one size does not fit all” when it comes to health-related communication. Responses should be tailored, contextualized, and person-centered, particularly in addressing concerns unique to women.